Valorization of Olive Mill Wastewater by Membrane Processes to Recover Natural Antioxidant Compounds for Cosmeceutical and Nutraceutical Applications or Functional Foods - Alberto Alfano; Luisana Corsuto; Rosario Finamore; Maria Savarese; Filomena Ferrara; Salvatore Falco; Giuseppe Santabarbara; Mario De Rosa; Chiara Schiraldi (MDPI AG, 2018)
Olive oil boasts numerous health benefits due to the high content of the monounsaturated fatty acid (MUFA) and functional bioactives including tocopherols, carotenoids, phospholipids, and polyphenolics with multiple biological activities. Polyphenolic components present antioxidant properties by scavenging free radicals and eliminating metabolic byproducts of metabolism. The objective of this research project was to recover the biologically active components rich in polyphenols, which include treatment of olive oil mills wastewater, and, at the same time, to remove the pollutant waste component resulting from the olive oil manufacturing processes. With specific focus on using technologies based on the application of ultra and nanofiltration membranes, the polyphenols fraction was extracted after an initial flocculation step. The nano-filtration permeate showed a reduction of about 95% of the organic load. The polyphenols recovery after two filtration steps was about 65% w/v. The nanofiltration retentate, dried using the spray dryer technique, was tested for cell viability after oxidative stress induction on human keratinocytes model in vitro and an improved cell reparation in the presence of this polyphenolic compound was demonstrated in scratch assays assisted through time lapse video-microscopy. The polyphenols recovered from these treatments may be suitable ingredients in cosmeceuticals and possibly nutraceutical preparations or functional foods.